Improving WASH Status and Knowledge in the Coastal Areas of Bangladesh - Hoque, Bilqis Amin; Khanam, Sufia; Siddik, Md. Abubakkor; Ahmed, Sohel; Shipon, Abu Zahid (Faculty of Geography, Universitas Gadjah Mada, 2025)
This action research aimed to improve the status of water, sanitation, and hygiene (WASH) and related knowledge in the coastal Kalia and Lohagara upazilas of Narail district in Bangladesh. The project offered a total of 606 safe water options, 950 household latrines, 50 latrines for disabled individuals, five community latrines, and 20 sanitation blocks. Further, created WASH awareness through organizing courtyard meetings and folk song events, distributing awareness posters, WASH pouts, school routines, school WASH posters, installing billboards, and painting community walls. Female adults from 534 randomly selected households’ were interviewed during the base-line survey and end-line survey. This study revealed that the rate of use of deep tube wells and hygienic latrine—that is, septic tanks and leak-free ring slab latrines—has increased substantially in both areas. Besides, perceptions about health problems associated with drinking arsenic-contaminated water improved considerably. Furthermore, knowledge about hygienic latrine improved by about 25 percentage points. Perception about hygienic hand washing and post-defecation hand washing (both hands with soap) practice improved but still needs to work on improving before eating both hand washing with soap practice. Therefore, suggesting further education and reinforcement on the importance of washing hands with soap before eating. This study also explored that knowledge about the mode of diarrheal transmission improved at the end of the intervention. However, to maintain favourable impressions and overcome difficulties in comprehending diarrhoea transmission mechanisms, particularly with regard to water, further education and focused interventions are needed.Received: 2024-07-28 Revised: 2024-08-20 Accepted: 2025-03-11 Published: 2025-05-26